2019
DOI: 10.1016/j.jamda.2019.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Nutritional Screening Tools for Community-Dwelling Older Adults: A Systematic Review and Meta-Analysis

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 59 publications
1
39
1
Order By: Relevance
“…The MNA-SF used in the present study has been shown to have a specificity of 100%, sensitivity of 97.9%, and diagnostic accuracy of 98.7% in undernutrition prediction as compared to the MNA-long version [ 32 ]. Further validation of the MNA-SF against the MNA-SF in a recent systematic review and meta-analysis found that the MNA-SF (cut-off point ≤11) had a sensitivity of 0.95 (0.75–0.99) and specificity of 0.95 (0.85–0.99) in detecting community-dwelling older adults at risk of malnutrition [ 59 ]. Additionally, a study of 155 older adults with a mean age of 78 years exploring the relationship between the MNA-SF and other comprehensive nutritional assessment measures, found that the MNA-SF had a stronger correlation with anthropometric and biological markers ( p < 0.01) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MNA-SF used in the present study has been shown to have a specificity of 100%, sensitivity of 97.9%, and diagnostic accuracy of 98.7% in undernutrition prediction as compared to the MNA-long version [ 32 ]. Further validation of the MNA-SF against the MNA-SF in a recent systematic review and meta-analysis found that the MNA-SF (cut-off point ≤11) had a sensitivity of 0.95 (0.75–0.99) and specificity of 0.95 (0.85–0.99) in detecting community-dwelling older adults at risk of malnutrition [ 59 ]. Additionally, a study of 155 older adults with a mean age of 78 years exploring the relationship between the MNA-SF and other comprehensive nutritional assessment measures, found that the MNA-SF had a stronger correlation with anthropometric and biological markers ( p < 0.01) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further validation of the MNA-SF against the MNA-SF in a recent systematic review and meta-analysis found that the MNA-SF (cut-off point ≤11) had a sensitivity of 0.95 (0.75-0.99) and speci city of 0.95 (0.85-0.99) in detecting community-dwelling older adults at risk of malnutrition [58]. Additionally, a study of 155 older adults with a mean age of 78 years exploring the relationship between the MNA-SF and other comprehensive nutritional assessment measures, found that the MNA-SF had a stronger correlation with anthropometric and biological markers (p<0.01) [59].…”
Section: Discussionmentioning
confidence: 99%
“…It includes decrease in food intake, weight loss and BMI, as well as interviews for mobility and mental/cognitive health problems, and is often used for community-dwelling older adults. 24 MUST is scored by weight loss, nutrient deficiency as a result of disease and BMI. It has a short time-to-completion due to its small number of items, and has face validity, content validity, construct validity and predictive validity.…”
Section: Discussionmentioning
confidence: 99%
“…MNA‐SF screens for malnutrition risk using six items of multifaceted information. It includes decrease in food intake, weight loss and BMI, as well as interviews for mobility and mental/cognitive health problems, and is often used for community‐dwelling older adults 24 . MUST is scored by weight loss, nutrient deficiency as a result of disease and BMI.…”
Section: Discussionmentioning
confidence: 99%